A study of the influence of spacing within rows and seed tuber size upon the yield of the potato crop : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agriculture Science at Massey University - Anang, Husin (Massey University, 1966)
The potato is one of the main food crops grown in New Zealand, and has been established since the time of European settlement In the early years production was concerned mainly with meeting the demands of the growing population. This resulted in a rapid and steady inorease in the total acreage grown. However, in the last decade, increase has been gained largely through intensification of orop areas rather than their extensification. Consequently, a diminishing increase in acreage grown has resulted. The above pattern is clearly illustrated in the following figures (extracted from Farm Production Statistics of New Zealand 1963 - 1964) [From Introduction]
Keywords: Potatoes; Spacing; Yields